Evaluation of novel thiophene branched polystyrene as insulator layer in organic electronic device - Gunaydin, Okan; Demir, Ahmet; Atahan, Alparslan; Yardim, Tayfun; Yucedag, Ibrahim (Elsevier Science Bv, 2019)
A novel thiophene branched polystyrene copolymer (PS-Th) was successfully synthesized and well characterized. Two different Organic Field Effect Transistor (OFET) devices were fabricated by using this novel PS-Th material and polystyrene (PS) as insulator materials and main performance parameters of the devices such as mobility (mu(FET)), on/off ratio (I-on/off), and threshold voltage (V-Th) were compared. Consequently, our results indicated that PS-Th copolymer was efficiently working as dielectric material for OFETs. Moreover, mu(FET) significantly enhanced (approx. 3.7 times) compared to the PS based OFET device while V-Th and I-on/off were slightly increasing. This situation can be explained by well organized molecular arrangement at the dielectric-semiconductor interface via thiophene-thiophene interaction between semiconductor material Poly(3-hexylthiophene-2,5-diyl) (P3HT) and insulator material PS-Th chains. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Organic field-effect transistor (OFET); Insulator materials; Polymer electrode; Electrical properties; Polystyrene; Thiophene